Components of Professional Development as Predictors of Academic Research Productivity in Universities in Anambra State (UNIZIK Journal of Educational Management and Policy, 2026)
This study examined components of professional development as predictors of academic staffresearch productivity in universities in Anambra State, Nigeria. Anchored on Human CapitalTheory, the study adopted a correlational research design. The population comprised 3,276academic staff from Nnamdi Azikiwe University and Chukwuemeka Odumegwu OjukwuUniversity, with a sample of 356 selected through multi-stage sampling. Data were collectedusing the Professional Development Questionnaire (PDQ) and Academic Staff ResearchProductivity Questionnaire (ASRPQ), and analysed using multiple regression and ANOVA.Findings revealed that professional development components research grants, fellowshipprogrammes, sabbatical leave, workshops, and conference attendance jointly have a strongand significant predictive value (R = 0.846; R² = 0.715) on research productivity. Workshopsand conferences were the strongest predictors. The study concluded that effective professionaldevelopment programmes significantly enhance research productivity and recommendedincreased funding, strengthened fellowships, and greater participation in research-focusedactivities.
Keywords: Professional development, research productivity, academic staff, universities